2011
DOI: 10.1074/jbc.m110.191924
|View full text |Cite
|
Sign up to set email alerts
|

Hrs Recognizes a Hydrophobic Amino Acid Cluster in Cytokine Receptors during Ubiquitin-independent Endosomal Sorting

Abstract: Hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs) is a component of the ESCRT-0 protein complex that captures ubiquitylated cargo proteins and sorts them to the lysosomal pathway. Although Hrs acts as a key transporter for ubiquitin-dependent endosomal sorting, we previously reported that Hrs is also involved in ubiquitin-independent endosomal sorting of interleukin-2 receptor ␤ (IL-2R␤). Here, we show direct interactions between bacterially expressed Hrs and interleukin-4 receptor ␣ (IL-4R␣),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…A mutated form of Hrs, deleted from the UIM, presented a similar increase of tyrosine phosphorylation after stimulation by IFN-α ( Fig. 1E), suggesting that IFNAR1 ubiquitination was not required for Hrs interaction and phosphorylation, as already reported for other cytokine receptors (16). This result is also consistent with our finding that only IFN-α and not IFN-β promotes the interaction of IFNAR1 with Hrs, whereas both IFN-α and IFN-β can induce the ubiquitylation of IFNAR1 subunits (17,18).…”
Section: Ifnar1 Interacts With Hrs At the Early Endosomesupporting
confidence: 76%
“…A mutated form of Hrs, deleted from the UIM, presented a similar increase of tyrosine phosphorylation after stimulation by IFN-α ( Fig. 1E), suggesting that IFNAR1 ubiquitination was not required for Hrs interaction and phosphorylation, as already reported for other cytokine receptors (16). This result is also consistent with our finding that only IFN-α and not IFN-β promotes the interaction of IFNAR1 with Hrs, whereas both IFN-α and IFN-β can induce the ubiquitylation of IFNAR1 subunits (17,18).…”
Section: Ifnar1 Interacts With Hrs At the Early Endosomesupporting
confidence: 76%
“…While HGS is better known for its ability to target the ubiquitin-modified cargoes [ 67 , 68 ], it has also been shown to recognize a motif of clustering hydrophobic amino acids in cytokine receptors IL-2Rb and IL-4Ra, in an ubiquitin-independent manner [ 69 , 70 ]. Similarly, our result from the co-IP experiment suggested that the HGS protein could be associated with the assembly domain of HBc in a manner independent of the potential ubiquitination sites in both HGS (UIM domain) and HBc (K7, K96) ( Fig 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…33 In these cargos, Hrs recognizes a hydrophobic amino-acid cluster, which is utilized as an ubiquitin-independent sorting signal. 34 Therefore, SARA exhibits all the structural requirements to form an alternative to Hrs ESCRT-0 complex. Indeed, not only do the Hrs-and TSG101independent pathways exist 35,36 but also totally ESCRT-independent mechanisms of multivesicular endosome biogenesis have been predicted to occur.…”
Section: Discussionmentioning
confidence: 99%